Verifiable Credentials: Transforming Digital Identity in the Real World - Ravikanth Reddy Gudipati (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative impact of Verifiable Credentials (VCs) in revolutionizing digital identity management across various sectors. The article examines the core components, technical architecture, and real-world implementations of VC systems, highlighting their role in enhancing security, privacy, and operational efficiency. The article investigates adoption challenges and solutions, focusing on enterprise integration and regulatory compliance. Additionally, it explores emerging technologies, including AI integration and post-quantum security, along with government initiatives shaping the future of digital identity. The article demonstrates that VCs offer a paradigm shift in how organizations approach identity verification, enabling secure, privacy-preserving, and decentralized credential management while significantly reducing administrative overhead and fraud risks.